2015
DOI: 10.1364/boe.6.004912
|View full text |Cite
|
Sign up to set email alerts
|

Color-coded LED microscopy for multi-contrast and quantitative phase-gradient imaging

Abstract: We present a multi-contrast microscope based on color-coded illumination and computation. A programmable three-color light-emitting diode (LED) array illuminates a specimen, in which each color corresponds to a different illumination angle. A single color image sensor records light transmitted through the specimen, and images at each color channel are then separated and utilized to obtain bright-field, dark-field, and differential phase contrast (DPC) images simultaneously. Quantitative phase imaging is also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Fortunately, a thin label-free phase object often satisfies this assumption. Previous studies [33][34][35][36] have demonstrated phase retrieval techniques by tuning multiwavelength illumination for nondispersive objects. Even a phase imaging method under a white-light source has been proposed.…”
Section: Framework Of Wavelength Multiplexed Fourier Ptychographic MImentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, a thin label-free phase object often satisfies this assumption. Previous studies [33][34][35][36] have demonstrated phase retrieval techniques by tuning multiwavelength illumination for nondispersive objects. Even a phase imaging method under a white-light source has been proposed.…”
Section: Framework Of Wavelength Multiplexed Fourier Ptychographic MImentioning
confidence: 99%
“…Even a phase imaging method under a white-light source has been proposed. 37 These methods [33][34][35][36][37] assume that the specimen maintains similar transmission properties across a large bandwidth. In our strategy, the differences of wavelength-dependent resolution vary the sizes of the circular regions in the Fourier plane.…”
Section: Framework Of Wavelength Multiplexed Fourier Ptychographic MImentioning
confidence: 99%
“…Assuming a linearized model for a weakly scattering sample, the DPC phase retrieval problem becomes a single-step deconvolution process using the phase contrast transfer function (PTF). By implementing DPC with a programmable LED array [19,20,30] or a programmable LCD panel [31], we are able to realize dynamic QPI along arbitrary axes of asymmetry, without any mechanical moving parts.…”
Section: Introductionmentioning
confidence: 99%
“…However, artifacts of phase reconstruction still cannot be completely avoided, since DPC's PTF is not circularly symmetric with only 2-axis measurements. Efforts have been made toward developing high speed, or even single-shot QPI mechanisms, such as color-coded DPC based on wavelength multiplexing [30,32,33]. Other efforts have been made to achieve isotropic DPC by either using more time-consuming intensity measurements along different illumination angles (12-axis) [20] or replacing the conventional half-circle illumination aperture with 3-axis radially asymmetric patterns [34] or 2-axis gradient amplitude patterns [35].…”
Section: Introductionmentioning
confidence: 99%
“…In time-coded LED array microscopy, multi-contrast images such as bright-field, dark-field, and differential phase contrast (DPC) are acquired by temporally changing the illumination patterns of the light source [18]. In color-coded LED array microscopy, three color-coded illumination allows simultaneous acquisition of bright-field, dark-field, and DPC images at a single shot [19].…”
Section: Introductionmentioning
confidence: 99%